1998
DOI: 10.1038/sj.leu.2400968
|View full text |Cite
|
Sign up to set email alerts
|

V-myc in a simple, single gene retroviral vector causes rapid induction of leukemia and concomitant apoptosis following bone marrow transplantation

Abstract: We have previously developed an in vivo model of leukemogenesis utilizing mice reconstituted with genetically modified bone marrow cells. Based on those studies, a new single gene retroviral vector has been engineered which efficiently transfers vmyc into immature murine bone marrow cells. All reconstituted mice developed leukemia with a short latency period (5-11 weeks). In addition to hyperproliferation associated with elevated levels of PCNA, extensive apoptosis was also observed in all leukemic animals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…However, during the transformation process by v-Myc, the proliferative function out-balances the apoptotic function. This phenomenon also occurs in vivo in mice reconstituted with immature bone marrow cells infected with retroviruses expressing v-myc (Dolnikov et al, 1998). All mice develop leukemia with a short latency period (5 ± 11 weeks).…”
Section: Mechanisms Of Transformation and Tumor Progressionmentioning
confidence: 83%
“…However, during the transformation process by v-Myc, the proliferative function out-balances the apoptotic function. This phenomenon also occurs in vivo in mice reconstituted with immature bone marrow cells infected with retroviruses expressing v-myc (Dolnikov et al, 1998). All mice develop leukemia with a short latency period (5 ± 11 weeks).…”
Section: Mechanisms Of Transformation and Tumor Progressionmentioning
confidence: 83%
“…3 Recently, we have also shown that expression of v-myc in primary murine bone marrow cells induces a similar dual effect: hyperproliferation and apoptosis were observed both in vitro and in vivo, the latter when v -myc ± expressing cells were used to reconstitute the hematopoietic system of lethally irradiated mice. 4 Increased expression of the tumor-suppressor gene p53 was observed in v-myc ± transformed cells in this reconstitution model. 4 Induction of p21 WAF1 , known to be a downstream effector of p53 and responsible for p53-mediated growth -suppressing activity, 5 was not observed in that reconstitution model.…”
mentioning
confidence: 96%
“…4 Increased expression of the tumor-suppressor gene p53 was observed in v-myc ± transformed cells in this reconstitution model. 4 Induction of p21 WAF1 , known to be a downstream effector of p53 and responsible for p53-mediated growth -suppressing activity, 5 was not observed in that reconstitution model. 4 It was unclear why p53 accumulation induced by v -myc resulted in apoptosis rather than in p21 WAF1 induction and consequent growth arrest.…”
mentioning
confidence: 96%
See 2 more Smart Citations